PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS THINK PAIR SHARE MENINGKATKAN KEAKTIFAN PESERTA DIDIK DI SMAN 1 KUTA UTARA - Lalita Manohari; Ni Kadek Rini Purwati (Widyadari, 2023)
The discovery learning model based on think pair share is a learning model that provides space for students to be active in the learning process. This study aims to determine the application of think pair share-based discovery learning models in increasing student activity. This type of research is classroom action research with the Kemmis & McTaggart research design. The location of this research was SMAN 1 Kuta Utara for class XII Mipa 4 students with a total of 38 students as research subjects. The data analysis technique was carried out in a quantitative descriptive manner. The results of the data analysis show that the application of the think pair share-based discovery learning model can increase the activity of students with completeness in cycle I of 68.4% and increase in cycle II with completeness of 84.2%. Based on the results of data analysis, it can be concluded that the application of the think pair share-based discovery learning model can increase the activity of students.